SAFETY AND DISTRESS RESPONSE SYSTEM IN NIGERIA‘S INTERNATIONAL AIRPORTS (2014)
Airports require complete safety initiatives with a maximum of 20 minutes response time to distress situation. They are therefore regulated by International Civil Aviation Organisation (ICAO) standards. However, in Nigeria, airport safety and distress response have been of great concern due to inadequate infrastructure. This study, therefore, examined safety facilities and response capability to distress situations in Nigeria international airports. The effects of haphazard spatial developments within the airports and their environments were also examined. The available infrastructure for safety and distress response initiatives were considered using ICAO check-list to determine their adequacy. Four international airports namely: Murtala Muhammed (Lagos), Aminu Kano (Kano), Nnamdi Azikwe (Abuja), and Port Harcourt were purposively selected. Three questionnaires were administered to 618 airport operators, 369 users and 462 neighbours in soliciting information on various aspects of safety and distress response initiatives including terminal buildings, navigational aids, runways and fire-fighting equipment and adequacy of staff training for operating Safety Management Systems (SMS) effectively. This was complemented with Key Informant Interview (KII) with 12 technical staff from 5 airport operators. Satellite imagery data were used to acquire spatial information on the airports. Descriptive statistics were used to analyse data on adequacy of safety facilities, staff training and distress responsiveness. Pearson correlation was used to determine the relationship between safety infrastructure and airport age. Analysis of Variance was used to determine variations in airport operators‘ safety awareness as recommended by ICAO. The KII data were content analysed, while raster model was used to determine the landuse pattern. Analysis were done at p<0.05. Functionality of safety facilities fell short of ICAO standards in all the airports by 30%, 25%, 20% and 10% in Lagos, Kano, Port-Harcourt and Abuja respectively. A positive relationship existed between airport age and obsolescence of safety infrastructure (r=0.12). Lagos airport had the most obsolete safety facilities. KII also revealed breakdown of infrastructure in the airports. There were significant variations in safety awareness among airport operators (F=11.95). Safety awareness was highest among the staff of Federal Airports Authority of Nigeria (34.9%) and lowest among airport handling agents (12.2%). Ninety-one percent of airport operators sampled indicated distress response as being poor. Response time varied from 30 minutes in Abuja to 54 minutes in Lagos. Sixty percent of the users considered airport service quality as very low. Forty-six percent of airport operators indicated that they had no training since employed. Spatial analysis of the airports and their environment showed that Lagos and Kano airports suffered safety threats from poor waste management and chaotic traffic patterns. Safety and distress response capacity was relatively low in all the international airports investigated. There is an urgent need for the airports to be managed in line with international standards. Staff training should also be prioritised and spatial developments around airport s need to be controlled. Keywords: Airport safety, Distress response, Spatial development, Civil aviation standards, Nigerian international airports. Word Count: 463